Pulmonary Perfusion and Ventilation during Cardiopulmonary Bypass Are Not Associated with Improved Postoperative Outcomes after Cardiac Surgery - Rodriguez-Blanco, Yiliam F.; Gologorsky, Angela; Salerno, Tomas Antonio; Lo, Kaming; Gologorsky, Edward (Frontiers in Cardiovascular Medicine, 2016)
Objectives Clinical trials of either pulmonary perfusion or ventilation during cardiopulmonary bypass are equivocal. We hypothesized that to achieve significant improvement in outcomes both interventions had to be concurrent. Design Retrospective case-control study Settings Major academic tertiary referral medical center Participants 274 consecutive patients who underwent open heart surgery with cardiopulmonary bypass 2009 - 2013. Interventions The outcomes of 86 patients who received pulmonary perfusion and ventilation during cardiopulmonary bypass were retrospectively compared to the control group of 188 patients. Measurements and Main Results Respiratory complications rates were similar in both groups (33.7% vs. 33.5%), as were the rates of postoperative pneumonia (4.7% vs. 4.3%), pleural effusions (13.9% vs. 12.2%) and re-intubations (9.3% vs. 9.1%). Rates of adverse postoperative cardiac events including ventricular tachycardia (9.3% vs. 8.5%) and atrial fibrillation (33.7% vs. 28.2%) were equivalent in both groups. Incidence of sepsis (8.1% vs. 5.3%), postoperative stroke (2.3% vs. 2.1%), acute kidney injury (2.3% vs. 3.7%) and renal failure (5.8% vs. 3.7%) were likewise comparable. Despite similar transfusion requirements, coagulopathy (12.8% vs. 5.3%, p=0.031) and the need for mediastinal re-exploration (17.4% vs. 9.6%, p=0.0633) were observed more frequently in the pulmonary perfusion and ventilation group, but the difference did not reach the statistical significance. ICU and hospital stays, and the ICU readmission rates (7.0% vs. 8.0%) were similar in both groups. Conclusions Simultaneous pulmonary perfusion and ventilation during cardiopulmonary bypass were not associated with improved clinical outcomes.